Analysis of Waste Management Processes Based on Peer Interaction - Haruki Agustina; Herdis Herdiansyah; Habibulloh Adinegoro (Postgraduate, University of Mataram, 2023)
Peers advisory is important to help improving individual behavior, including waste-management and handling activities. The data analyzed in this study were derived from primary data collection on some populous provinces in Indonesia, along with waste-management problem. A survey has been conducted on more than 2,000 observations at individual level, gathered from 563 household to examine how social and education affect the probability of a person to follow correct waste-handling actions: put trash righteously. This study found that urban citizens in Indonesia are probably 1.7 times more likely to follow correct waste-handling actions, if they’re have been taught in environmental caring. This study also found that peers’ advice in terms of environmental caring will affect people 3.77 times more likely to put trash righteously. Overall, this study found that peer’s socialization environment is important in reshaping human’s behavior on handling wastes. In addition, good habits formed during childhood, and self-initiative behavior has not also been important enough to solve waste-handling problems.